2007
DOI: 10.1002/edn.79
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of a diabetes disease management programme with a central role for the diabetes nurse specialist

Abstract: Background: In the region of Maastricht, The Netherlands, a disease management programme (DMP) for patients with diabetes mellitus was implemented. The programme aims to improve quality of care within existing budgets. To achieve this, diabetes nurse specialists (DNSs) were given a central role within a multidisciplinary team of care providers. This study describes the cost-effectiveness of this approach. Aim: To measure the incremental cost-effectiveness of a diabetes DMP, with a central role for the diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 117 publications
(127 reference statements)
2
1
0
Order By: Relevance
“…The results of our study suggest that nurse specialists are more than capable of taking a centralized role in these teams, which is in accordance with earlier findings (Vrijhoef et al. 2001b, Vrijhoef 2002, Steuten et al. 2007).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The results of our study suggest that nurse specialists are more than capable of taking a centralized role in these teams, which is in accordance with earlier findings (Vrijhoef et al. 2001b, Vrijhoef 2002, Steuten et al. 2007).…”
Section: Resultssupporting
confidence: 93%
“…This is in consensus with the findings in a primary care setting by Vrijhoef et al. (2001b), Steuten et al. (2007) and Buchan (Buchan 2005) and in a hospital‐based setting by Houweling et al.…”
Section: Discussionsupporting
confidence: 91%
“…The exceptions were a weighted-average gross wage rate [43], a median wage rate [29], and the actual wage rate of respondents [36]. Seven studies reported using the age-group gender-based productivity cost per hour from the Dutch Costing Manual [52,54,60,[66][67][68]. The method of valuation of work time forgone could not be ascertained in the remaining four studies.…”
Section: Methods Of Estimating Productivity Costs Using the Friction mentioning
confidence: 97%